POSITION INDICATOR DETERMINATION IN STRATEGIC MANAGEMENT OF NANJING YUNJIN CULTURAL HERITAGE FOR CREATIVE ECONOMY - Yanling, Qi; Sodbhiban, Pichai; Suriyakarn, Pornwipa (Asia Pacific Journal of Religions and Cultures, 2025)
The strategic management of Nanjing Yunjin's cultural heritage must integrate its deep cultural significance and religious symbolism to maintain authenticity while appealing to modern markets. Leveraging these elements can enhance its role in the creative economy, attracting interest from both cultural enthusiasts and tourists. This article explores the strategic management of Nanjing Yunjin, a traditional Chinese silk tapestry, within the framework of the creative economy. It identifies key position indicators that can enhance the preservation and promotion of Yunjin's cultural heritage while integrating it into modern markets. By examining the interplay between cultural significance, religious symbolism, and contemporary economic trends, the study offers insights into how traditional cultural assets can be strategically managed to boost their economic value and global appeal. The findings provide a comprehensive approach for leveraging Nanjing Yunjin’s heritage to strengthen its role in the creative economy. This article presented (1) intangible cultural heritage, and (2) position indicator determination in strategic management of Nanjing Yunjin cultural heritage for creative economy.